PENGARUH PERILAKU KERJA KREATIF SEBAGAI VARIABEL INTERVENING PADA HUBUNGAN ANTARA GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN IKLIM KERJA DENGAN KINERJA GURU (STUDI PADA GURU SMA NEGERI DI KOTA SEMARANG) - Fadhil Aksoni; Intan Ratnawati (Faculty of Economics and Business | Universitas Diponegoro, 2020)
This study aims to analyze the effect of creative work behavior as an intervening variable on the relationship of transformational leadership styles and work climate with performance. This research consists of two independent variables, one dependent variable and one intervening variable. The independent variable in this research is transformational leadership style and work climate. The dependent variable in this study is employee performance. The intervening variable in this study is creative work behavior. The population in this study were all high school teachers in the city of Semarang. The sample uses simple random sampling, amounting to 112 respondents. Data collection techniques were carried out using a questionnaire. Analysis of research data using SEM (Structural Equation Modeling) analysis which is operated through the AMOS 24.0 program. The results of this study indicate that the transformational leadership style and work climate do not significantly influence employee performance. But creative work behavior has a significant positive effect on employee performance and transformational leadership style and work climate has a significant positive effect on creative work behavior.